Depression Among Patients with Type 2 Diabetes Mellitus: Prevalence and Associated Factors in Hue City, Vietnam - Tran NMH; Nguyen QNL; Vo TH; Le TTA; Ngo NH (Diabetes, Metabolic Syndrome and Obesity, 2021)
Nhu Minh Hang Tran,1 Quang Ngoc Linh Nguyen,1 Thi Han Vo,1 Tran Tuan Anh Le,1 Ngoc Ha Ngo2 1Department of Psychiatry, Hue University of Medicine and Pharmacy, Hue University, Hue, Thua Thien Hue, Vietnam; 2Preventive Medicine, Hue University of Medicine and Pharmacy, Hue University, Hue, Thua Thien Hue, VietnamCorrespondence: Nhu Minh Hang TranDepartment of Psychiatry, Hue University of Medicine and Pharmacy, Hue University, 346/1 Phan Chu Trinh, Hue, Thua Thien Hue, VietnamTel +84905108019Email tnmhang@hueuni.edu.vnBackground and Aims: Depression is common in people with type 2 diabetes mellitus. The association of depression and diabetes has negative effects on patients. This study investigated the prevalence of depression in individuals with type 2 diabetes mellitus and examined the social, psychological and clinical factors associated with depression.Patients and Methods: The study included 216 inpatients with type 2 diabetes mellitus at the Department of Endocrinology and Neurology, Hue Central Hospital and the Department of General Internal Medicine, Hue University Hospital. This descriptive cross-sectional study evaluated depression using the Patient Health Questionnaire-9 (PHQ-9). Data were collected on patients’ socio-demographic factors such as sex, age, marital and economic status, level of education and clinical factors including duration of type 2 diabetes mellitus, fasting blood glucose, HbA1C, comorbidities or complications as well as health behavior including alcohol consumption, smoking and physical activities. Logistic regression was used to analyze the factors associated with depression in patients with type 2 diabetes mellitus.Results: 23.2% of the patients had depression. The rates of severe, moderate and mild depression were 0.5, 0.9 and 21.8%, respectively. Multivariate logistic regression analysis indicated several factors associated with depression in participants, including age under 60 years, poor economic status, unstable or part-time work, having stress during the past year, without/poor treatment adherence to type 2 diabetes mellitus, and engaging in heavy physical activity or physical activity less than three days per week.Conclusion: The prevalence of depression among patients with type 2 diabetes mellitus is high. Endocrinologists should be made aware of the increased risk of depression in this patient population and screening individuals for relevant risk factors is highly recommended.Keywords: depression, type 2 diabetes mellitus, prevalence, risk factors